Antioxidants 2019
DOI: 10.5772/intechopen.84822
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antioxidative Effects of Kolaviron on Reproductive Function in Streptozotocin-Induced Diabetic Wistar Rats

Abstract: The present study investigated the effects of Kolaviron (KV) on the testicular and epididymal tissue antioxidant status in streptozotocin (STZ)-induced diabetic rats. Diabetes was induced by a single intraperitoneal injection of STZ at 50 mg/ kg body weight. The antioxidant status was studied by evaluating epididymal and testicular levels of malondialdehyde (MDA), a lipid peroxidation (LPO) marker, and the activities of catalase (CAT) glutathione peroxidase (GPX) and superoxide dismutase (SOD) were also assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Using animal studies, we have also reported the association between obesity-induced hypertension and male infertility. Obese-hypertensive rats presented with increased levels of serum inflammatory cytokines when compared with control ( 130 ). Our studies on the effects of long-term obesity on male reproductive functions suggested that the instigator of the molecular and proteomic modifications includes: an increase in the production of ROS, elevated stress proteins levels and higher levels of redox and inflammatory proteins.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using animal studies, we have also reported the association between obesity-induced hypertension and male infertility. Obese-hypertensive rats presented with increased levels of serum inflammatory cytokines when compared with control ( 130 ). Our studies on the effects of long-term obesity on male reproductive functions suggested that the instigator of the molecular and proteomic modifications includes: an increase in the production of ROS, elevated stress proteins levels and higher levels of redox and inflammatory proteins.…”
Section: Discussionmentioning
confidence: 97%
“…Several other population-based studies have shown the association between male infertility and hypertension ( 125 127 ). Animal studies have also thrived in this aspect of reproductive research and have provided evidence that hypertension is associated to male infertility ( 128 130 ). Akinyemi et al reported a significant decrease in serum total testosterone and reduced sperm progressive motility in hypertensive rats.…”
Section: Hypertension-induced Os In Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation